Peran Pelaksanaan Pengelolaan Kelas SD Negeri Bigaran - Gita Royani, Eflina; Wijayanto, Sukma (Prosiding University Research Colloquium, 2021)
From the above problems, the purpose of this study is to assist teachers in good classroom management, having comfortable classrooms, neat spatial arrangement and the use of media in learning to achieve learning objectives. This research was conducted in Bigaran State Elementary School. This study was designed using a qualitative research type with the hope of improving the student learning process. The data analysis used is inductive which is used as an understanding of the data obtained. The data that can be collected are in the form of words, pictures, and numbers. The subjects of this study were fourth grade students at SDN Bigaran and the object of the research was the application of classroom management at SDN Bigaran. The research carried out was observing the classroom, where the sitting position was arranged in such a way, the cleanliness of the room, the decorations in the classroom. The teacher asks students to paste the student’s work, there are pictures of heroes, pictures of Indonesian culture, maps in such a way that the classroom does not look boring to students. Based on the results of interviews with classroom teachers, students found that some students were able to follow and adjust conditions to the classroom environment. That way it will be easy for teachers in classroom management settings so that it will support the realization of the learning objectives to be achieved.